Um Novo m?todo de gera??o de sinais complexos - Caputo, Robinson Gaudino (2006)
ABSTRACT: In this work new applications in digital systems, encryption systems, data transmission, etc., through a new mathematical approach are described. This work presents some new important DNAx technique contributions to mathematics, physics and engineering fields. First of all the DNAx equations are defined and applied to definition of Delta of Dirac function, Unit Step Function and Non Periodic Pulse Function (Gate function). The concept of (OWA) Operational Window Aperture is introduced to allow the synthesis of complex signals in a easy way. A new transform concept that permits to map the points of time domain set to the mathematical domain set through polynomial function, is introduced. This transformation process allows to use polynomial process to develop new applications in digital signals systems. The DNAx function shows the viability to create sinusoidal wave functions through a addition of square waves with controlled distortions and creating a viability of new modulation process.